PENERAPAN PEMBAGIAN WARIS DI ADAT BATAK SIMALUNGUN DALAM PERSPEKTIF HUKUM WARIS ADAT - Ruth Angel; Aarce Tehupeiory; Haposan Sahala Raja Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Statutory law is a law that includes forms of statutory regulations that have been enacted and compiled and are generally applicable to Indonesian society, such as criminal law, civil law, commercial law, and others. Customary law is the law of growth and development in human life, without reality, living according to the desires and thoughts of the Indonesian people. Customary law is a law that is growing and developing day by day, the law itself exists in society according to changes in society itself. In the life of Indonesian society, it is very important for law enforcers, defenders and legal observers to know and understand living customary law in order to enforce the law harmoniously and fairly for the Indonesian people. The relevant legal theory in answering this issue is Hans Kelsen's theory of justice law regarding justice and peace and justice and legality. Then, the next theory used is the theory of protection by Soekanto that legal protection is basically protection given to legal subjects in the form of legal instruments. Based on this theory, it is the basis for analyzing the distribution of Batak customary inheritance. The type of research used in this study is empirical research, namely legal research that uses a system of observation, interviews, and document collection. The approach used is a historical and conceptual approach. The data used are primary and secondary data. Primary data is collected through observation and interviews while secondary data is obtained from primary, secondary, and tertiary legal materials.